2000
DOI: 10.1597/1545-1569(2000)037<0281:csbcwa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Children with and without Cleft Lip and Cleft Palate, Part 1: Cephalometric Analysis

Abstract: The study group presented a significant increase in the extension of the head on the neck, forward position of the cervical spine, and a decrease in the curvature of the cervical spine in comparison with the children without clefts. These results are more relevant considering that the study group also presented higher significant values of lower facial height than children without clefts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…There was only one comparative study regarding the facial morphology of 2 groups of complete unilateral cleft lip and palate Brazilian children 12 . The findings of the present study showed that patients undergoing cleft repair surgery during childhood have a jaw development decreased compared to patients without cleft, corroborating other studies conducted in children and adults 1,[14][15][16][17][18][19][20][21][22] . Regarding the interaction age x cleft, the results were similar to those found by Gomide et al 16 who observed that retrusion of the maxilla is common feature of Brazilian individuals with cleft lip and palate in both genders, becoming more noticeable with advancing age in the pre and post-puberty [19][20][21] .…”
Section: Discussionsupporting
confidence: 92%
“…There was only one comparative study regarding the facial morphology of 2 groups of complete unilateral cleft lip and palate Brazilian children 12 . The findings of the present study showed that patients undergoing cleft repair surgery during childhood have a jaw development decreased compared to patients without cleft, corroborating other studies conducted in children and adults 1,[14][15][16][17][18][19][20][21][22] . Regarding the interaction age x cleft, the results were similar to those found by Gomide et al 16 who observed that retrusion of the maxilla is common feature of Brazilian individuals with cleft lip and palate in both genders, becoming more noticeable with advancing age in the pre and post-puberty [19][20][21] .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have also reported the maxillary retrusion, the vertical growth pattern, the inferior hyoid bone position, and the larger craniocervical angulations found in the BCLP group analyzed in this study (Dahl, 1970;Bishara et al, 1976Bishara et al, , 1978Bishara et al, , 1985Vargervik, 1983;Semb, 1991;Bardach et al, 1992;Heidbuchel et al, 1994;da Silva Filho et al, 1998;Zúñiga et al, 2000;Rosenstein et al, 2003;Kaduk et al, 2003;Rose et al, 2003). The maxillary retrusion is attributed mainly to the surgical treatment, since untreated BCLP patients have a rather protruded maxilla (Ortiz-Monasteiro et al, 1966;BooChai, 1971;Pruzansky and Friede, 1975;Bishara et al, 1976;da Silva Filho et al, 1998).…”
Section: Discussionsupporting
confidence: 55%
“…Zúñiga et al. (25) compared the curvature of the cervical spine in children with cleft lip and palate with children without clefts. They found that the cleft children had significantly increased extension of the head and also a forward position of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%